Acceptability of a minimally invasive perinatal/paediatric autopsy: healthcare professionals' views and implications for practice. (4th March 2013) - Ben‐Sasi, K.; Chitty, L. S.; Franck, L. S.; Thayyil, S.; Judge‐Kronis, L.; Taylor, A. M.; Sebire, N. J.
ABSTRACT Background Perinatal autopsy provides essential clinical information, including cause of death; yet, autopsy rates have steadily declined because of parental refusal. Technology now enables less invasive alternatives to traditional autopsy and may increase the acceptability of post‐mortem examination. Objective This study aimed to examine the relative acceptability among healthcare professionals of a minimally invasive autopsy (MIA; magnetic resonance imaging and laparoscopic‐guided tissue sampling), compared with standard autopsy. Methods This study was questionnaire‐based survey of healthcare professionals working in clinical settings where paediatric and perinatal deaths occur. Results Of 250 questionnaires distributed, 224 were returned (90% response rate). Autopsy was generally perceived as acceptable. Demographic factors affecting acceptability included ethnicity and religion but not professional role. MIA compared favourably with traditional autopsy, 50% of respondents reporting both equally acceptable, 40% reporting MIA more acceptable and 10% less acceptable. Healthcare professionals agreed that having a MIA option would make it easier to discuss autopsy with parents (P < 0.001). Conclusion Less invasive autopsy appears an acceptable alternative to traditional autopsy for most respondents. Healthcare professionals should be aware that ethnic and religious opinions influence their own views on autopsy decisions and should be mindful of this when discussing autopsy with parents. Further research is needed to determine parental opinions. © 2013 John Wiley & Sons, Ltd.